2011
DOI: 10.1074/jbc.m111.223669
|View full text |Cite
|
Sign up to set email alerts
|

Polyubiquitination Events Mediate Polymethylmethacrylate (PMMA) Particle Activation of NF-κB Pathway

Abstract: The pathologic response to implant wear-debris constitutes a major component of inflammatory osteolysis and remains under intense investigation. Polymethylmethacrylate (PMMA) particles, which are released during implant wear and loosening, constitute a major culprit by virtue of inducing inflammatory and osteolytic responses by macrophages and osteoclasts, respectively. Recent work by several groups has identified important cellular entities and secreted factors that contribute to inflammatory osteolysis. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
(32 reference statements)
3
18
0
Order By: Relevance
“…In addition, strontium also attenuates the protein levels of NFATc1 and MMP-9 as compared with untreated controls. Several authors have demonstrated that blocking NF-κB pathway obviously diminished wear-particle-induced osteoclastogenesis1819. Similarly, our results showed that strontium significantly decreased particle-induced osteoclast formation and bone resorption.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, strontium also attenuates the protein levels of NFATc1 and MMP-9 as compared with untreated controls. Several authors have demonstrated that blocking NF-κB pathway obviously diminished wear-particle-induced osteoclastogenesis1819. Similarly, our results showed that strontium significantly decreased particle-induced osteoclast formation and bone resorption.…”
Section: Discussionsupporting
confidence: 84%
“…RANKL plays an activated role in osteoclastogenesis by connecting the corresponding receptor RANK on the membrane of osteoclast precursors16. Briefly, binding of RANKL to RANK initiates the recruitment of TNF receptor-associated factor 6 and prompts induction of the nuclear factor-κB (NF-κB) pathway which induces osteoclastogenesis finally to result in the peri-prosthetic osteolysis171819.…”
mentioning
confidence: 99%
“…Recent studies have revealed that numerous ubiquitin ligases are involved in regulation of transcriptional factors including the MAPK signaling pathway and NF-B signaling pathway [29,30]. Moreover, some members of the TRIM family of ubiquitin ligases have been shown to be involved in the regulation of these signaling pathways [23,28,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB plays a critical role in immune response, inflammatory reaction, and cell growth regulation by controlling the expression of various crucial cytokines, adhesion molecules, and chemokines (Kwak et al, 2011;Yamanaka et al, 2011;Byeon et al, 2012). Moreover, NF-κB is also the main regulator of inflammation and oxidative stress reactions (Goldin et al, 2006;Gratas-Delamarche et al, 2014), and its activation is also involved in cell proliferation and apoptosis.…”
Section: Dissussionmentioning
confidence: 99%
“…NF-κB with a sequence-specific dimeric structure is an important type of transcription factor existing widely in mammalian cells, which can bind specifically to a variety of cellular gene-promoter and -enhancer sequences (Kwak et al, 2011;Yamanaka et al, 2011;Byeon et al, 2012). Its activation, as a regulator of inflammation and oxidative stress reaction, is also involved in the process of cell proliferation and apoptosis (Goldin et al, 2006;GratasDelamarche et al, 2014).…”
Section: Effect Of Naringin On P65 Protein Expression In Gp120-treatementioning
confidence: 99%